Sequence and functional characterization of the human purine nucleoside phosphorylase promoter. - Jonsson, J J (1991)
Purine nucleoside phosphorylase (PNP) is a ubiquitously expressed enzyme which contributes to the catabolism and recycling of nucleotides. To characterize the promoter region of the human PNP gene, the nucleotide sequence from a BamHI site located in the 5' untranslated region extending 2237 bp upstream to an XbaI site was determined. The transcriptional start site as determined by primer extension was 119 bp upstream of the coding sequence and consisted of a 5'-CA-3' dimer with A at +1. A TATA box was identified -24 to -29 bp upstream of the transcriptional start site. A CCAAT pentamer sequence in the inverted orientation was present at -51 to -55 bp and two GC rich regions were identified at -68 to -81 bp and -168 to -187 bp. Progressive 5' deletions of the 5' flanking region were fused to the chloramphenicol acetyltransferase (CAT) reporter gene and transient expression measured after transfection of murine NIH/3T3 fibroblasts. A 91 bp promoter (the shortest tested) provided CAT activity at 60% the level of a 216 bp promoter, possibly due to removal of the GC rich region between -168 and -187 bp. Longer promoters resulted in CAT expression at similar or lower levels than the 216 bp promoter indicating that this region contained all of the 5' flanking sequences affecting transcription from the PNP promoter.